Design of Styrofoam Cutting Machine Based on CNC 2 Axis Using Hot Wire - Fahrizal Fahrizal; Muhammad Fikriatul Aslam; Nurhikmah Anwar; Isminarti Isminarti; Andi Fitriati (Journal of Computer Engineering, Electronics and Information Technology, 2022)
The development of the creative industry in the manufacture of decorations from styrofoam materials is increasing rapidly, the need for a 2-axis CNC-based automatic styrofoam cutting machine (Computer Numerical Control) using hot wire can facilitate the process of cutting styrofoam in large quantities and uniformly with machine drive on the X and Y axes. The purpose of this study is to design and manufacture a CNC based styrofoam cutting machine that can be programmed so that it can facilitate the cutting of styrofoam in large quantities and uniformly with movement on the X and Y axes. The method used is an experimental method in which the G-Code processing process is sent to the software which then produces 2 axis movements, namely on the X and Y axes. Then the styrofoam cutting process is continued using a hot wire whose temperature has been regulated using voltage and current which produces styrofoam cutting according to the size of the styrofoam used, which is 88 cm long, 42 cm high with a thickness of 2 cm and the accuracy level obtained for the X axis of 99.84% and the Y axis of 99.91%.